Letramentos acadêmicos na educação a distância (EaD): desenvolvimento de um curso digital - Mezzalira, Tailine Guarezi (2024)
The present study, linked to the Professional Master’s in Networked Educational Technologies Course, under the research field of Networked Educational Technologies Management of the Federal University of Santa Maria - RS, in general aims to analyze the literate practices of students of the University’s Distance Education Letters Course, through their participation and interactions in a course about academic literacies. In order to develop the research, we anchored ourselves in the sociocultural perspective of literacies, which considers this concept as an amalgam of social practices, mediated by reading and writing activities, and moulded by cultural influences, social structures, and power relationships (STREET, 1984). We have also based ourselves in theoretical studies which involve the area of Distance Education, and Networked Educational Technologies. Through this, we sought to: produce digital didactic materials as teaching and learning tools, identify the challenges and potentials of materials related to the appropriation of academically literate practices in the context of a Distance Education Course, as well as evaluate if the academics broadened their view towards academic literacies and developed a collaborative learning/formation. In methodological terms, the research classifies as qualitative and applied in nature, as the generation of data was done through the application of the product resulting from the dissertation, which consists in a course about academic literacies. During the course, two semi-structured questionnaires were applied and observations about the literacy practices explored by 12 (twelve) individuals were made through the usage of diaries. The analysis of data evidenced important particularities about the process of adaptation and development of an academic identity of the research’s subjects, allowing us to identify their perceptions in relation to the challenges imposed by the academic context. Through this, we verified that the practice of synchronous interaction shows itself fundamental to the development of more significant learning in this teaching modality. The data also revealed that the constructive singularities of each individual’s identity, as well as the Discourses that cut through their literacy journey, are determinant to the construction of their Distance Education practices.